Net neutrality under usage-based pricing: A game-theoretic analysis with user loyalty - Tuan Anh Trinh; Imre Abos; Gyula Sallai (International Telecommunications Society (ITS), 2012)
Network neutrality issue has been recently received a great attention from the research community, the industry and the network regulators alike. From the European perspectives, the net neutrality issue is increasingly important because it is also part of the Digital Agenda 2020 recently approved by the European Commission [1, 2]. Until now, usage-based pricing and network neutrality have been considered as two different research problems and very few network neutrality researchers examine usage-based pricing as a main consideration. In addition, the user behaviour such as user loyalty issue should be seriously taken into consideration because users will have an increasingly more important role in the operation and management of the network. In this paper, we address the net neutrality issue by investigating the usage-based pricing in presence of user loyalty from the game-theoretic perspective. The contributions of the paper are twofold. First, we provide game-theoretic models for the interaction among the stakeholders under usage-based pricing under the presence of customer loyalty. Based on the models, we compute the Nash equilibrium prices of the pricing games and discuss the consequences and the impact on net neutrality. Results show both positive and negative impacts of usage-based pricing on net neutrality. From the user perspective, the usage-based pricing does not show advantage over simple flat-rate pricing. On the positive side, our results also suggest that under certain circumstances cooperation between broadband providers can make the network be more profitable and yet sustainable. Based on the results, we discuss the practical feasibility of applying usage-based pricing for net neutrality under the presence of user loyalty.
Keywords: 330